Efektifitas Mom’s Bra-Tem Compress Pada Ibu Nifas Dengan Payudara Bengkak - Diana Mufidati; Puji Handayani; Mayangsari, Rr. Nindya; Hamsiah; Serni Ramadhani (Bunda Edu-Midwifery Journal (BEMJ), 2024)
The research "Effectiveness of Mom’s Bra-Tem Compress for Postpartum Mothers with Breast Engorgement" is a government program aimed at addressing breast engorgement. Demographic data in Indonesia (SDKI) indicates that in 2012-2013, 55% of breastfeeding mothers suffered from breast engorgement and mastitis, caused by inadequate breast care. Breast engorgement often occurs during lactation. If oxytocin release is not smooth, breast milk secretion is inhibited, leading to swelling of the mammary glands and causing discomfort. Therefore, immediate and continuous intervention is needed in midwifery care for postpartum mothers with breast engorgement. The purpose of the Mom’s Bra-Tem Compress, a bra filled with jelly, is to reduce breast engorgement in a simple, comfortable, efficient, and effective way that can be used anywhere and anytime. The method used is quasi-experimental with a pretest-posttest control group design. The research subjects are postpartum mothers with breast engorgement. The sampling technique used is random sampling. The instrument used to assess the level of engorgement is the Six Point Engorgement Scale (SPES). Data analysis was conducted using univariate and bivariate analysis with Wilcoxon signed-rank test and Mann-Whitney test. The results showed that the use of Mom’s Bra-Tem Compress had an impact on postpartum mothers.